Financial Literacy: A Study of Rural People in Malwa Region of Punjab - Bansal, Monica (Gyan Management Journal, 2019)
Financial Literacy has been playing a very important role in the lives of people, especially in the developed nations. A plethora of multifarious and complicated financial services and products at the disposal compounded by an acute absence of financial knowledge and financial planning among the masses pose a huge hindrance in the process of smart saving, rational borrowing and wise investment which might ensure better retirement benefits and heightened risk cover. The development of the nation does not necessarily guarantee the financial literacy of its people. However, various national and international agencies are working towards promoting awareness in this matter by conducting workshops, programmes and seminars etc. on financial education. A lack of financial literacy has huge adverse effects on the financial decision making of the individual as it leads to a lack of financial knowledge which results in an inability to plan finances in an optimally profitable and desirable manner. On top of it, it impacts the macro-economic concerns adversely as well as it lesser participation in financial markets, leads to wealth inequality, trenching financial growth and hampering the overall financial health of a nation. The present research is expected to contribute immensely to the socio economic growth sustenance and overall development of the society.